Association between earnings management and non-GAAP measures - Pontes, Gleison de Abreu; Lemes, Sirlei; Silva, Jéssica Rayse de Melo; Costa, Patrícia de Souza (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To investigate the association between Abnormal Book-Tax Differences (ABTD) and the measures of Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA), and Adjusted EBITDA, as reported by Brazilian publicly traded companies. Methodology: Use of canonical correlation on data manually collected from Reference Forms regarding EBITDA and Adjusted EBITDA, as well as information from financial statements needed to estimate ABTD, which were obtained from the Economatica® platform, analyzing the behavior of the variables during the period from 2012 to 2021. Results: The study’s results reveal significant associations between the variables, highlighting that ABTD has a greater influence on EBITDA than on Adjusted EBITDA. This finding suggests that accounting and tax earnings management practices, which can be simultaneously captured in ABTD, go beyond mandatory financial information, making them not directly observable in the values disclosed by companies in measures such as EBITDA. Contributions of the Study: The study contributes to the literature by demonstrating that ABTD can be used for the joint assessment of financial performance measures, revealing possible indications of earnings manipulation. The analysis of the association between ABTD and EBITDA alerts investors and other users to the need for caution when interpreting mandatory and voluntary information disclosed by companies. The study also paves the way for the development of more sophisticated models in future research, deepening the understanding of ABTDA’s influence on measures beyond EBITDA.